The problem of mind-body interaction and the causal principle of Descartes's Third Meditation - Sepetyi, D.; Сепетий, Дмитро Петрович (My University, 2021)
The article analyses recent English publications in Cartesian studies that deal with two prob-lems: (1) the problem of the intrinsic coherence of Descartes’s doctrine of the real distinction and interaction between mind and body and (2) the problem of the consistency of this doctrine with the causal principle formulated in the Third Meditation. The principle at issue is alterna-tively interpreted by different Cartesian scholars either as the Hierarchy Principle, that the cause should be at least as perfect as its effects, or the Containment Principle, that the cause should contain all there is in its effects. The author argues that Descartes’s claim (in his argument against the scholastic doctrine of substantial forms) that it is inconceivable how things of differ-ent natures can interact does not conflict with the acknowledgement of interaction between things of different natures in the case of soul and body. The case is made that Cartesian mind-body interaction can agree with both the Hierarchy Principle and the Containment Principle, because the Principle is about total and efficient cause, whereas in the interaction, mental and brain states are only partial (and plausibly, in the case of brains states, occasional) causes. In particular, in the case of the causality in the brain-to-mind direction, the mind is conditioned by brain states to form the corresponding specific ideas on the basis of its innate general ideas of movements, forms, colours, etc. Eventually, for Descartes, the most natural way to deal with worries about the possibility of mind-brain interaction is to rely on God’s omnipotence, which certainly enables Him to arrange for such interaction. У статті, на матеріалі англомовних декартознавчих досліджень, обговорюються дві про-блеми: (1) проблема внутрішньої несуперечливості вчення Декарта про реальну відмінність і взаємодію ума й тіла та (2) проблема узгодженості цього вчення зі сформульованим у Тре-тій Медитації каузальним принципом. Зазначений принцип тлумачиться різними декартоз-навцями або як Принцип Ієрархії, згідно з яким причина має бути не менш досконалою, аніж її наслідки, або як Принцип Вміщення, згідно з яким причина має містити в собі все, що міститься в її наслідках. Автор доводить, що Декартова апеляція (в аргументі проти схо-ластичного вчення про субстанційні форми) до незбагненності того, як речі різної природи можуть взаємодіяти, не суперечить визнанню взаємодії між речами різної природи у випа-дку душі й тіла. Обґрунтовано, що і Принцип Ієрархії, і Принцип Вміщення можуть узго-джуватися з визнанням взаємодії між умом і тілом, оскільки Принцип стосується повної дієвої причини, тоді як у взаємодії, ментальні стани та фізичні стани мозку є лише частко-вими причинами. Зокрема, оскільки йдеться про спричинення в напрямку від тіла до ума, ум під впливом станів мозку формує відповідні специфічні ідеї на основі вроджених зага-льних ідей рухів, форм, кольорів тощо. Зрештою, у питанні про можливість психофізичної взаємодії для Декарта природно покладатися на всемогутність Бога, який напевно спромо-жний зробити так, щоб ум і тіло (мозок) людини взаємодіяли.
Проблема психофізичної взаємодії та каузальний принцип Третьої Медитації Декарта
Sepetyi D. - http://orcid.org/0000-0003-2110-3044
Keywords: substance; real distinctness; dualism; efficient cause